Development of peripheral neuropathy and its association with survival during treatment with nab-paclitaxel plus gemcitabine for patients with metastatic adenocarcinoma of the pancreas: A subset analysis from a randomised phase III trial (MPACT). (January 2016) - Goldstein, David; Von Hoff, Daniel D.; Moore, Malcolm; Greeno, Edward; Tortora, Giampaolo; Ramanathan, Ramesh K.; Macarulla, Teresa; Liu, Helen; Pilot, Richard; Ferrara, Stefano; Lu, Brian
Abstract: Background: In a phase III trial in patients with metastatic pancreatic cancer (MPC), nab -paclitaxel plus gemcitabine ( nab -P/Gem) demonstrated greater efficacy but higher rates of peripheral neuropathy (PN) versus Gem. This exploratory analysis aimed to characterise the frequency, duration, and severity of PN with nab -P/Gem in the MPACT study. Patients and methods: Patients with previously untreated MPC received nab -P/Gem or Gem. PN was evaluated using a broad-spectrum group of Standardised Medical Dictionary for Regulatory Activities Queries (SMQ) and graded by National Cancer Institute Common Terminology Criteria for Adverse Events (NCI CTCAE) version 3.0. A case report form was completed by physicians on day 1 of each cycle (also graded by NCI CTCAE version 3.0). Results: In the nab -P/Gem arm, 227/421 patients (54%) experienced any-grade PN and 70 (17%) experienced grade III PN. No grade IV PN was reported. Most early-onset PN events were grade I, and treatment-related grade III PN occurred in 7% of patients who received up to three cycles of nab -P. Of those who developed grade III PN with nab -P/Gem treatment, 30 (43%) improved to grade ≤I (median time to improvement = 29 days) and 31 (44%) resumed therapy. Development of PN was associated with efficacy; median overall survival in patients with grade III versus 0 PN was 14.9 versus 5.9 months (hazard ratio, 0.33; P  < .0001). Conclusions: nab -P/Gem was associated with grade III PN in a small percentage of patients. PN development was associated with longer treatment duration and improved survival. Grade III PN was reversible to grade ≤I in many patients (median ≈ 1 month) NCT00844649 . Highlights: Most neuropathy observed with nab -paclitaxel plus gemcitabine ( nab -P/Gem) was grades ≤II and none was grade IV. ≈ 16% of patients who received nab -P/Gem had dose modifications due to neuropathy. Many patients who developed grade III neuropathy improved to grade ≤I in ≈ 1 month. Patients who developed grade III versus lower grades of neuropathy had a longer median overall survival.